2020
DOI: 10.1111/ggi.14022
|View full text |Cite
|
Sign up to set email alerts
|

Family members' concerns about relatives in long‐term care facilities: Acceptance of visiting restriction policy amid the COVID‐19 pandemic

Abstract: The policy enforcing visiting restriction during the COVID-19 pandemic may cause feelings of social isolation among residents in long-term care facilities. This study aimed to explore family members' concerns for their relatives during the lockdown period, assess their level of acceptance of the visiting restriction policy and determine the associated factors. Methods: From the 156 family members interviewed, demographic data, satisfaction with overall care quality, worry and concerns for their relatives, acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 28 publications
4
32
0
Order By: Relevance
“…Women, younger carers, people with existing financial difficulties, and Black, Asian, and minority ethnic (BAME) carers have been found to be at greater risk of negative outcomes (e.g., financial difficulties, health, loneliness) (Bennett, Zhang, & Yeandle, 2020a, 2020b, 2020cBlueCross BlueShield 2020;Cagnin et al, 2020;Carers UK, 2020a; Rosalynn Carter Institute for Caregiving, 2020). Carers of people living in residential care settings have found it difficult to remain in contact with their relatives, have been worried about their health status and the quality of care they receive, and have feared negative long-term implications due to the prolonged social isolation experienced by their relatives (Baxter, 2020;Carers UK, 2020b;Hosking, Maccora, & McCallum, 2020;USA-gainstAlzheimer's, 2020;Yeh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Women, younger carers, people with existing financial difficulties, and Black, Asian, and minority ethnic (BAME) carers have been found to be at greater risk of negative outcomes (e.g., financial difficulties, health, loneliness) (Bennett, Zhang, & Yeandle, 2020a, 2020b, 2020cBlueCross BlueShield 2020;Cagnin et al, 2020;Carers UK, 2020a; Rosalynn Carter Institute for Caregiving, 2020). Carers of people living in residential care settings have found it difficult to remain in contact with their relatives, have been worried about their health status and the quality of care they receive, and have feared negative long-term implications due to the prolonged social isolation experienced by their relatives (Baxter, 2020;Carers UK, 2020b;Hosking, Maccora, & McCallum, 2020;USA-gainstAlzheimer's, 2020;Yeh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Foremost, human resources issues had a profound impact on the lack of communication between the LTCFs and family members. Communication challenges during COVID-19 were especially prominent as families sought information about their relative (Leaman & Azios, 2021;Ting-Chun et al, 2020;Tupper et al, 2020). Interestingly, McArthur et al (2021) reported that quick deployment of communication strategies in LTCFs in New Brunswick resulted in residents being protected from the mental health consequences of lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Years of theorizing and study about aging and family life relationships (Silverstein & Giarrusso, 2010), family as care partners (Canadian Foundation for Healthcare Improvement, 2020; Government of the United Kingdom, 2021; Tupper et al, 2020), person-centred care (Bouchoucha & Bloomer, 2021; Canadian Foundation for Healthcare Improvement, 2020), the role of families in LTCFs given the shortage of care providers (Gwyther, 2001;Ting-Chun et al, 2020) seem to have completely been ignored in the face of this pandemic. Empirical research confirms the need to consider family caregivers as extended clients of LTCFs (Gwyther, 2001) given the emotional burden that usually accompanies having a family member in a LTCF (Strang, Koop, Dupuis-Blanchard, Nordstrom, & Thompson, 2006;Ting-Chun et al, 2020). Families often feel isolated (Gwyther, 2001) while worrying about the health and well-being of their relative (Strang et al, 2006).…”
Section: Families and Ltcmentioning
confidence: 99%
“…Although not being a ban, which is not supported by Swedish law, the visitor restrictions initiated a public debate on the risk of social isolation and the negative consequences that might have, 10 and they were lifted in October 2020 based on the risk of negative consequences of isolation instigated by lengthy visitor restrictions. 11 So far, research has mainly focused on family members’ experiences of the restrictions, 12 13 and the impact they may have on people living in nursing homes is poorly understood, with no primary data on their experiences.…”
Section: Introductionmentioning
confidence: 99%